Ketimpangan Gender Dalam Pembagian Kerja Guru di Sekolah: Studi Kasus di SMPN 1 Sumbawa Barat - Adib Al-Mufakhir (Insight: Indonesian Journal of Social, Humanity, and Education, 2025)
This research aims to understand the reality of gender inequality in the division of teacher work at SMPN 1 West Sumbawa, with a focus on the factors that influence gender inequality and the implications of gender construction in teachers' work at school. This research uses qualitative research methods by collecting data from various sources, such as books, journals and articles, to analyze gender gaps in school work. The research also uses an interview approach, namely collecting data from sources as the main source and various other sources such as books, journals and articles, as well as carrying out a data collection process to obtain valid data regarding gender gaps in school work. This study highlights the importance of gender equality in the division of work for teachers in schools by involving the community, educational institutions and high school officials to evaluate and contextualize the situation regarding gender inequality in the division of work for teachers in schools. There are two types of gender inequality identified: first, female teachers who are often placed in desk jobs or jobs that are classified as soft, second, female teachers who are often positioned in less strategic jobs with a smaller role and influence on schools so that policy is not a priority and only serves as an additional option or as a complement. These two problems are a fact that in the concept of division of labor, female teachers often experience injustice. [Penelitian ini bertujuan untuk memahami realitas ketidaksetaraan gender dalam pembagian kerja guru di SMPN 1 Sumbawa Barat, dengan fokus pada faktor-faktor yang mempengaruhi ketidaksetaraan gender dan implikasi konstruksi gender dalam pekerjaan guru di sekolah. Penelitian ini menggunakan metode penelitian kualitatif dengan mengumpulkan data dari berbagai sumber seperti buku dan artikel jurnal untuk menganalisis kesenjangan gender dalam pekerjaan sekolah. Penelitian juga menggunakan pendekatan wawancara, yaitu pengumpulan data dari narasumber sebagai sumber utama dan berbagai sumber lain seperti buku, jurnal, dan artikel, serta melakukan proses pengumpulan data untuk memperoleh data valid mengenai kesenjangan gender dalam pekerjaan sekolah. Studi ini menyoroti pentingnya kesetaraan gender dalam pembagian kerja guru di sekolah dengan melibatkan masyarakat, lembaga pendidikan, dan pejabat tinggi sekolah untuk mengevaluasi dan mengkontekstualisasikan situasi mengenai ketidaksetaraan gender dalam pembagian kerja guru di sekolah. Ada dua jenis ketidaksetaraan gender yang teridentifikasi: pertama, guru perempuan yang sering ditempatkan pada pekerjaan di balik meja atau pekerjaan yang tergolong lembut, kedua, guru perempuan yang sering di posisikan pada pekerjaan yang kurang strategis dengan peran dan pengaruh terhadap sekolah yang lebih kecil sehingga kebijakannya tidak menjadi prioritas dan hanya berkesan sebagai opsi tambahan atau sebagai pelengkap saja. Dua persoalan ini merupakan sebuah fakta bahwa dalam konsep pembagian kerjanya guru perempuan sering mendapat ketidakadilan.]